Hospital Closures and Short-Run Change in Ambulance Call Times - Sookti Chaudhary; Alison Davis; Kenneth Troske; SuZanne Troske (Institute of Labor Economics (IZA), 2019)
We measure one aspect of how access to emergency care through ambulance services changes for patients when a hospital closes. We empirically estimate the time needed to transport a patient to an emergency department in an ambulance in the period immediately after the hospital closes. We find urban patients in zip codes where a hospital closes have a small change in transportation time, where rural patients average an estimated 15.7 additional minutes – a 46% increase compared to the year before the closure. This increase is primarily the result of an almost 100 percent increase in the time it takes to transport a patient from the location of the incident to the hospital. The impact on rural Medicare-eligible patients is even larger. We find no change in the time it takes ambulances to arrive at an incident and only a small change in the time spent at the scene.
Keywords: I11; I14; I18; R10; 330; ambulance; hospital closure; access to care; rural vs urban